Effect of pre-immunization by killed Mycobacterium bovis and vaccae on immunoglobulin E response in ovalbumin-sensitized newborn mice - (:unkn) unknown (MUNKSGAARD INT PUBL LTD, 1999)
A recently advanced hypothesis suggests that decreased exposure to T-helper (Th) 1-inducing agents causes Th2-biased differentiation in response to concomitant allergens. We therefore examined the effect of pre-immunization with killed Mycobacterium bovis and killed M. vaccae which are known to be very potent inducers of Th1 immune response, on serum IgE response in ovalbumin (OVA)-sensitized newborn mice. Eighty-four newborn Balb/c mice were divided into four groups and were immunized intraperitoneally 24 h after birth with 50 mu l of 5 x 10(4) colony-forming units (c.f.u.) of killed M. bovis in group I (M. bovis group, n = 19) with 25 mu l of 2.5 X 10(8) c.f.u. of killed M. vaccae plus 25 mu l of 5 x 10(4) c.f.u. of killed M. bovis in group II (M. vaccae + M. bovis group, n = 28) and with 50 mu l of only phosphate-buffered saline (PBS) in group III (no mycobacterial immunization, n = 18). No injection was applied to mice in group IV (control group, n = 19). Starting from 8 weeks of age, all mice except the control group were sensitized with 0.5 ml of 20 mg/ml OVA administered intraperitoneally 7 times every other day. Thirty days after the final injection, all animals except those in the control group were challenged with an aerosol of 2 mg/ml OVA. Forty-eight hours later, blood was collected from all mice for determination of serum IgE levels. A statistically significant difference was observed in the serum total IgE levels between groups III and IV (p = 0.0099), indicating that the mice were successfully sensitized with OVA. Serum total IgE values of the female mice in M. bovis group were found to be significantly lower than group III (p = 0.009), while no difference was observed in males. Serum total IgE levels of the M. vaccae + M. bovis group were found to be significantly lower than group III both in male and female mice (p < 0.0001 and p = 0.0001, respectively). Female values were even lower than controls (p = 0.0092). Preimmunization in the newborn period with killed M. bovis alone or in addition to M. vaccae may potentially be helpful in down-regulating an IgE response.
Keywords: atopy; IgE; Mycobacterium vaccae; Balb; c mice; newborn; T-HELPER; TUBERCULOSIS; INFECTION; CELLS; BCG; TH1; IMMUNOTHERAPY; PREVALENCE; SYMPTOMS; ALLERGY